Замулене межиріччя: межа як конструент ідентичності в романі «Месопотамія» Сергія Жадана - Ганошенко, Юрій Анатолійович; Ganoshenko, Y. (Миколаїв : Вид-во ЧНУ ім. Петра Могили, 2017)
Статтю присвячено проблемі філософського й літературознавчого оприявнення функціональності концептосфери межовості в процесах формування сучасної постмодерної ідентичності та специфіки її художнього втілення в літературному тексті. За допомогою герменевтичного, феноменологічного й психоаналітичного методів розкривається синтетична природа ідентичності у романі «Месопотамія» одного з найбільш впливових авторів сучасної української літератури Сергія Жадана з огляду на специфіку просторової складової формування тожсамості та побудови просторових параметрів побутування персонажа цього літературного твору; особливостей експлікації в художньому тексті індивідуальної постмодерної ідентичності; письменницьких стратегій відображення колективного рівня ідентичності літературного героя. Особливо розглянуто своєрідну жанрову природу твору, що теж вияскравлює специфіку ідентичності персонажа, яка виразно має ознаки «між» – лімінальності, дифузності, розмитості, гібридності. Статья посвящена проблеме философского и литературоведческо определения функциональности концептосферы границы (межи) в процессах формирования современной постмодерной идентичности и специфики ее художественного воплощения в литературном тексте. С помощью герменевтического, феноменологического и психоаналитического методов раскрывается синтетическая природа идентичности в романе «Месопотамия» одного из самых влиятельных авторов современной украинской литературы Сергея Жадана с точки зрения специфики пространственной составляющей формирования тожсамости и построения пространственных параметров бытия персонажа этого литературного произведения; особенностей экспликации в художественном тексте индивидуальной постмодерной идентичности; писательских стратегий отражения коллективного уровня идентичности литературного героя. Отдельно рассмотрено своеобразную жанровую природу произведения, которая также объясняет специфику идентичности персонажа, которая определенно имеет признаки «между» – лиминальности, диффузности, размытости, гибридности. The article is devoted to the problem of the artistic embodiment of individual and group identity. The subject of the study is the boundary as a concept and methodological principle in contemporary literary criticism, which helps to study the features of the reflection of identity. The study of the identity of modern Ukrainians is one of the most urgent problems of modern humanity studies. The literary potential of the study of identity has not yet been fully disclosed, and therefore the article is an actual study. The use of hermeneutic, phenomenological and psychoanalytical methods makes it possible to study the problem using a broader variety of approaches. The subject of the study is the novel Mesopotamia by one of the most famous writers of modern Ukrainian literature, Sergij Zhadan. The writer's strategies for the embodiment of identity in his novel are quite diverse and stimulate scientific interest. The article reveals the features of the construction of the artistic space in the novel and the mythologization of the narrative as a reflection of the liminal identity of the characters. This same hypothesis is confirmed by an analysis of the individual and collective identity of the heroes of Mesopotamia, which can be characterized as diffuse, fuzzy, and hybrid. Their identity is formed in a «between state» (between generations, between ideological systems, between cultures) and reflects a certain blockage at the border, the fuzziness and infantilism of the attitude to life, the society, and the environment. Separately analyzed is the synthetic genre nature of the novel, which specifically combines the epic and the lyrics, and blurs the boundaries between them. The writer's strategy is to direct the readers' reception in order to perceive the heroes of Mesopotamia in the context of blurring boundaries and being «between».
Заиленное межиречье: граница как конструент идентичности в романе «Месопотамия» Сергея Жадана
Intricate wordlimit: the boundary as identity construct in the novel Mesopotamia by Sergij Zhadan
Keywords: Українська література; ідентичність; межа; лімінальність; концепт; письменницька стратегія; жанрова специфіка; идентичность; граница; лиминальность; писательская стратегия; жанровая специфика; identity; boundary; liminality; concept; writer's strategy; genre specific